Information Systems Management — Modular Approach - Seppo Sirkemaa (IACSIT Press, 2022)
Information systems management can be a challenging task, especially in a smaller organization. In smaller organizations the resources tend to be limited, and often there are is no IT staff or expertize in the organization. Despite this, information systems need to be running without interruptions, and act as a robust infrastructure for business activities and processes. Management of information systems is needed, it should support business objectives and operations in the best possible way. Here we suggest modular approach to information systems management – mapping key domains and activities in the system, and working together with external service providers in order to provide a flexible information systems and infrastructures in the organization.